Kepemilikan ultimate perusahaan di Indonesia: Praktik Tunneling - Fadli Fendi Malawat; Condro Widodo (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2022)
The purpose of this study is to analyze the effect of separation control rights and cash flow rights on tunneling activities. control rights indicator is interpreted through a socioemotional perspective. Furthermore, the main focus of the research is to investigate the divergence between control rights and cash flow right by ultimate structure ownership on tunneling activities through the size of related party transactions (RPTs) from the agency theory. The regression analysis technique was used to test the hypothesis developed in the study, the population is manufacturing companies on the Indonesia Stock Exchange (IDX), with a sampling technique using a purposive sampling method. The results of the study prove a significant influence between control rights on tunneling activities, showing that the motivation for control rights is not socioemotional. Meanwhile, cash flow rights have a significant influence on tunneling activities. Furthermore, the results of the study provide empirical evidence that higher divergence can lead to greater tunneling activities. The theoretical contribution of this research is to visualize agency theory and socioemotional perspective. It is hoped that further research can examine company ownership in Indonesia from a socioemotional perspective.